Hubungan Karakteristik Individu, Komunikasi Pendidikan Seksual, Perilaku Hubungan Seksual, dan Akses Informasi dengan Tingkat Pengetahuan HIV/AIDS pada Remaja Laki-laki di Indonesia - Tisara Syafira Awanis; Erni Astutik; Hamzah Yasfi Akbar Sholihin (Media Gizi Kesmas, 2024)
Background: By the end of 2022, it was recorded that 39 million people worldwide having HIV, with higher transmission and mortality rates among men. Data in Indonesia in 2022 showed 58.95% of 52,955 HIV cases and 74.46% of 9,905 AIDS cases in Indonesia were male. Based on UNICEF data, 2.8 million adolescents and childrens have HIV. The level of HIV knowledge among male adolescents is lower than female adolescents, where low knowledge about HIV is a major factor in the high prevalence of HIV in adolescents Objective: This study aims to understand the relationship between individual characteristics, sexual education communication, sexual behavior, and access to information on the level of knowledge about HIV/AIDS among Indonesian male adolescents. Methods: The study used quantitative methods with secondary data from the Indonesia Demographic Health Survey (IDHS) in 2017, the dependent variable was the level of knowledge about HIV/AIDS and the independent variables consisted of age, residence, highest level of education, sex education communcation with others, history of sexual intercourse, and history of access to information through radio, TV, newspapers or magazines, and the internet. Analysis using STATA 14 application. Bivariate analysis used chi-square and multivariate analysis used multiple logistic regression. Results: Age, residence, highest level of education, sex education communication with others, history of sexual intercourse, listening to the radio, using the internet, and reading newspapers or magazines have an association with the level of HIV/AIDS knowledge of male adolescents. Based on multivariate analysis, respondents aged 20-24 years, living in urban areas, not communicating about sex education with others, having had sexual intercourse, listening to the radio, using the internet, and reading newspapers or magazines at least once a week had higher odds of having a high level of knowledge about HIV/AIDS. Conclusion: Communication with the right person directly can avoid misinformation. Sexual  experience can broaden understanding of HIV/AIDS, including basic knowledge about prevention and potential impacts, before engaging in it. One of the main sources of knowledge is information, by accessing various HIV/AIDS information through radio, internet use or reading newspapers and magazines, can increase the level of HIV/AIDS knowledge.